Kondisi Populasi Rafflesia patma Blume di Cagar Alam Pananjung Pangandaran Jawa Barat: Condition of Rafflesia patma Blume Population in Pananjung Pangandaran Nature Reserve, West Java - Husein Mukmin; Agus Hikmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2009)
Rafflesia patma Blume is placed as one of the CRB2c endangered status. It refers to the taxon who face the highest extinction in the short periode of time. The flower scarce is caused by a live factor of R. patma that need specific habitats such as physical and biotic factors. The habitats and population of R. patma will be charge on fluctuation due to the higher human activities and nature's changes. The study on population of R. patma in CA Pananjung Pangandaran (CAPP) was conducted. The results indicated that R. patma founded 312 individuals which distributed in 6 locations. This condition indicated that CAPP is suitable from R. patma. Keywords: Rafflesia patma, population, endangered, extinction, biotoc factor